The Relationship between Principals Instructional Leadership Practices and Students Academic Achievement of secondary schools in Banda Acheh Indonesia - Salleh, Mohamad Johdi; Hatta, Muhammad (2011)
The study presents the relationship between principals’ instructional leadership practices and students' academic achievement of secondary schools in Banda Aceh,Indonesia. The Principal Instructional Management Rating Scale (PIMRS) modified by Hallinger and Murphy (1985) and Latip (2006) was used as the data collection instrument through survey questionnaire. The respondents of this study were 12 principals and 163 randomly selected teachers of secondary schools Banda Aceh. The study used correlation statistical analysis based on interpretation of the Pearson Correlation (r) which provides the direction, significance, strength, and, considered as the most stable measure of correlation (Gay, 1992; Creswell 2008). There were twelve null hypotheses were formulated to examine the correlation of the two variables. This study found that there were only three job functions, namely, monitoring student progress, maintaining high visibility, and, developing and enforcing academic standards which had a significant relationship with students' academic achievement. It is hoped that this research will provide useful findings which will effectively assist the process of instructional leadership enhancement among principals and teachers of secondary schools in Banda Aceh in order to improve students' academic performance.